Investigation on the different types method of joining for automotive panel - Mohd Khairi, Ali (2007)
In this paper, the objective is to study Quality comparison between different type methods of joining in tailor welded blank and Selection the type of welding process used to make a taIlor blank. Tailor-welded blanks (TWBs) of the d!fèrent material and with different thickness combinations were welded together to form a single part before the formability process . Thus, SPCC steel sheets of thickness of 0.7 and SPHC steel sheet of thickness 1.2 were studied and combined to form TWBs .Different types of welding such as ,shield metal are welding(SMAW), metal inert gas we1dingMIG), tungsten inert gas welding(TIG) and laser beam welding was used to weld the tailor-made blanks before the formability tests of the uniaxial tensile test. The experimental findings show those TWBs of different types of welding shows different strength and also different elongation and the effect to the parent material. The uniaxial tensile tests show that there are no significant differences between the tensile strengths of T and their relative base metals.